The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19127198
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Substance Use in Latin America: A Scoping Review

Abstract: This scoping review aims to explore the interplay between substance use (SU) and HIV in Latin America (LA). Database searches yielded 3481 references; 196 were included. HIV prevalence among people who used substances (PWUS) ranged from 2.8–15.2%. SU definitions were variable throughout studies, and thus data were not easily comparable. In 2019, only 2% of new HIV infections were attributed to injection drug use (IDU) in LA. Factors associated with HIV among PWUS included being female, IDU and homelessness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 211 publications
0
8
0
1
Order By: Relevance
“…(7) Por otra parte, en relación a Latino américa se estima entre el 0,4 % y 3,9 % se obtiene conocimiento que estas cifras están en aumento. (8) Dentro de las sustancias de mayor consumo engloba el alcohol, cafeína, cannabis, alucinógenos, inhalantes, opioides, hipnóticos, sedantes, tabacos y estimulantes. (9) Además, representa un conflicto de interés a nivel económico, político, social e igualmente dentro de los factores más predisponentes para que se desencadene esta problemática son los efectos psicosociales, los mismo que engloban, desde enfermedades con alteraciones a nivel molecular y celular, accidentes o situaciones relacionadas a su entorno familiar.…”
Section: Introductionunclassified
“…(7) Por otra parte, en relación a Latino américa se estima entre el 0,4 % y 3,9 % se obtiene conocimiento que estas cifras están en aumento. (8) Dentro de las sustancias de mayor consumo engloba el alcohol, cafeína, cannabis, alucinógenos, inhalantes, opioides, hipnóticos, sedantes, tabacos y estimulantes. (9) Además, representa un conflicto de interés a nivel económico, político, social e igualmente dentro de los factores más predisponentes para que se desencadene esta problemática son los efectos psicosociales, los mismo que engloban, desde enfermedades con alteraciones a nivel molecular y celular, accidentes o situaciones relacionadas a su entorno familiar.…”
Section: Introductionunclassified
“…Substance use remains a robust predictor of HIV infection across resource-diverse contexts and settings (Allen, Myers, & Ray, 2015; Huff et al, 2022; Rumbwere Dube, Marshall, Ryan, & Omonijo, 2018; Shuper et al, 2010). Specifically, a recent systematic review found that injecting drugs, smoking crack-cocaine, and binge-drinking (as well as similar behaviors by one’s partner) predicted HIV infection among adults in high-income countries (Rumbwere Dube et al, 2018), while separate reviews similarly reported that injecting drugs and using stimulants (such as methamphetamines) contributed to HIV burden in lower-resource environments (El-Bassel, Shaw, Dasgupta, & Strathdee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a recent systematic review found that injecting drugs, smoking crack-cocaine, and binge-drinking (as well as similar behaviors by one’s partner) predicted HIV infection among adults in high-income countries (Rumbwere Dube et al, 2018), while separate reviews similarly reported that injecting drugs and using stimulants (such as methamphetamines) contributed to HIV burden in lower-resource environments (El-Bassel, Shaw, Dasgupta, & Strathdee, 2014). Pathways linking substance use to HIV infection include direct routes, such as needle sharing among people who inject drugs, and indirect routes, through behavioral disinhibition (e.g., through heavy alcohol use or stimulant use) in the form of condomless sex (El-Bassel et al, 2014; Heath, Lanoye, & Maisto, 2012; Huff et al, 2022; Rehm, Probst, Shield, & Shuper, 2017; Sandfort et al, 2017; Vosburgh, Mansergh, Sullivan, & Purcell, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 1 in 8 substance users lives with HIV, and that this number is 1.4 million people worldwide. HIV infection is 22 times more common in those with intravenous substance use compared to the general population (4). National Institute on Drug Abuse (NIDA) considers drug addiction and HIV to be intertwined epidemics, and emphasizes the close connection between substance addiction and hepatitis (NIDA, 2013) (1).…”
Section: Introductionmentioning
confidence: 99%